Роль окситоцину у формуванні пубертатних маткових кровотеч - Диннік, В. О. (Clinical Endocrinology and Endocrine Surgery, 2010)
174 girls with PUB aged 11−17 were examined to determine their oxytocine (O) level, the interrelations between O level and PG, gonadotropins, prolactin and estrogens. There was confirmed the participation of O in PUB pathogenesis. It was determined that at PUB the average findings of O (depending on the clinical group) were 33−56 % lower than the standard ones, which no doubt negatively affected the uterus contractile activity. It was revealed that in all the girls, even at normal O findings, certain disorders in PG, gonadotropins and estrogens production took place. Thus, there were revealed significant disorders in interrelations between O, PG, gonadotropins, PRL and steroid hormone production that confirmed the significant O role in the development of central disturbances at PUB.